Readers na formação dos alunos de língua inglesa - Topolski, Vera Márcia (2013)
This research investigates the usage of readers in the English language classroom as a pedagogical tool that can contribute to the student s formation as someone who enjoys reading in the foreign language. It is an applied research which starts bibliographical, bringing together different texts by Regina Zilberman and Tania Rösing (2009), Regina Zilberman (2005) and Affonso Romano de Sant Anna (2011), among other important theoreticians, for comparing their ideas on the reading subject, and it is also an action-research project, involving a group of students of a 9th grade of a municipal school in Passo Fundo, where the researcher is also the teacher. The project is developed through the application of a reading practice based on the adapted work of Charles Dickens Oliver Twist, retold by Sarah Gudgeon and illustrated by Maja Celija. It aims to motivate general reading enjoyment and, especially, in the English language, as well as to notice their involvement in the proposed activity through envisionments (as an activity to provide meaning) by Judith Langer (2005), with the intention of evaluating the validity of including readers in the English language classroom. The investigated subjects contributed with their envisionments during the development of the project and answered a final questionnaire. It is believed that reading practices which are based on those books can contribute significantly for the formation of readers in English, since graded reading facilitates comprehension, helping the students to acquire self-confidence and, possibly, pleasure when reading. For that, the teacher needs to propose activities related to the linguistic level and to the features of each group, enabling, this way, bigger confidence to the students and, yet, a delightful reading experience